From Promise to Proof: Revealing the Comparative Performance of RSV Vaccines Through Network Meta-Analysis - Madani, M. Iyad; Haq, Hilmi Amirul; Abdullah, Bryan Naufal (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: There is no consensus on the optimal vaccine platform for preventing respiratory syncytial virus (RSV) infection. Recent advances in RSV vaccine development aim to improve efficacy and safety across various platforms. This study aimed to compare the efficacy and safety of available RSV vaccines using a network meta-analytic approach to identify the most effective strategy for RSV prevention.Method: A systematic search was performed in PubMed, ScienceDirect, Cochrane, and Scopus up to November 2025 to identify randomized controlled trials (RCTs) of RSV vaccines in healthy populations. Ten RCTs were included, evaluating adenovirus vaccine, subunit vaccine, mixed subunit and adenovirus vaccine, subunit vaccine with AS01E, and placebo controls were included.  Analyses were conducted in RStudio using the netmeta package. Risk of bias was appraised using RoB 2.0 and certainty of evidence was assessed with CINeMA and the GRADE frameworks. Result and Discussion: This analysis demonstrated that the subunit vaccine with AS01E possesses superior efficacy in reducing RSV-related respiratory illness compared to placebo (RR = 0.22, 95% CI: 0.16 -- 0.31). This finding was reinforced by ranking analysis, which identified this intervention as the most effective (P-score = 0.916). No significant differences in safety profiles were observed across interventions, although precision was limited by wide confidence intervals and substantial heterogeneity. Conclusion: Subunit vaccines with AS01E demonstrated the highest efficacy for RSV prevention. However, their safety profile has not yet been clearly defined, and further research is needed to assess long-term effectiveness and monitor potential late adverse effects.